Chemical explosion isolation applied to small mills. Issue 2 (14th December 2014) - Taveau, Jérôme R.; Farrell, Thomas M.
<x xml:space="preserve">Abstract</x> Mills are used in many branches of the process industries (food, chemical, pharmaceutical, and energy). According to accident statistics, this type of equipment is also among the most likely places for a dust deflagration to occur: fine dust is continuously produced and suspended mechanical sparks or hot particles can be created during the milling operation, ignite an explosible atmosphere within the mill, or travel with the process flow into downstream equipment. Protection of both the mill and the interconnected equipment needs to be addressed for an effective explosion protection strategy. Since mills generally exhibit a fairly strong design, they are expected to withstand a dust explosion without any additional overpressure protection (in this case, high strength pipes need to be employed with). On the other hand, explosion isolation must be considered carefully, as a dust explosion can propagate through pipes and reach other equipment. The fact that reduced explosion pressure in a mill is typically an order of magnitude higher than in a vented enclosure poses some challenges to isolation techniques, and particularly chemical isolation barriers. An experimental investigation was carried out to verify the effectiveness of a chemical explosion isolation barrier applied to a small unvented vessel (representing a mill) equipped with long pipes. Dust was injected inside the pipes to promote flame propagation and create challenging conditions for the isolation barrier. Application limits, specifically focusing on installation distances, were studied. The effect of chemical isolation upon downstream pipe pressure development was also investigated. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 157–166, 2015